Implementasi Metode Naive Bayes Dalam Penyeleksian Karyawan untuk Penempatan Bagian Pemasaran - Eka Fitriani; Royadi Royadi; Atang Saepudin; Dian Ardiansyah; Riska Aryanti (Jurnal Teknik Komputer AMIK BSI, 2022)
Marketing is a job that has a scope of work on the promotion of a product, goods or service. The problem that always occurs in the company is that there is no department responsible for selecting reliable marketing employees. The existence of these problems resulted in the process of recruiting employees for the new marketing division which was still not carried out professionally. This can happen because there is no standard method to be able to support in assessing the selection of prospective employees in the marketing department, it is necessary to do an analysis related to the selection of employees in the placement of the marketing department. By holding the analysis process for employees in the placement of a new marketing division, it can be seen whether the prospective marketing division employee passes or does not pass. From the existing problems, a data mining classification method is used to predict the selection of employees for the Marketing section by using the nave Bayes method. After testing using the nave Bayes method, it produces an accuracy value of 87.22% and an AUC value of 0.920 with an Excellent Classification diagnostic level. So it can be concluded that using the nave Bayes method can be a good method for implementation in selecting employees for placement in the Marketing department.